Effects of age and playing tactics on the individual tactical behavior in U10 and U12 elite Spanish soccer players - González-Rodenas, J.; Pedrera, G.; Dorado, V.; Aranda-Malavés, R.; Tudela-Desantes, A.; De Matías-Cid, P. (Sports, 2022)
The aim of this paper was to explore the effects of age and playing tactics on the individual tactical behavior and performance in young soccer players. A total of 1247 individual possessions during 16 knockout matches from LaLiga Promises U12 tournament (n = 621) and LaLiga U10 Iscar Cup (n = 626) were analyzed by observational methodology. Multilevel and multivariate logistic regression models were created to explain the interdependent effects of age category and playing tactics on the individual tactical behavior and performance. Youth players performed most of their actions against defensive pressure (72.5%), during offensive support (91.3%) and receiving the ball facing forward (62.6%). The most frequent action was to receive and pass the ball (69.6%) and the level of offensive success was 56.9%. The multilevel mixed models revealed that U10 players presented higher odds of running with the ball vs. passing the ball (OR = 1.823; 95% CI: 1.333-2.493; p < 0.001) and lower odds of achieving offensive success (OR = 0.698; 95% CI: 0.525-0.928; p < 0.05) than U12 players. Regarding playing tactics, technical-tactical dimensions such as the players` body shape when receiving the ball, offensive support, defensive pressure, collective type of attack and type of technical action presented a significant and combined effect on the offensive success regardless of age category, playing position and match status. This study found tactical differences between U10 and U12 age categories and revealed important interactive effects of multiple tactical dimensions on the individual offensive behavior and performance in youth soccer players.